2009
DOI: 10.1055/s-0029-1233457
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Evaluation of Body Composition, Glucose Homeostasis and Lipid Profile of Male Rats Programmed by Maternal Protein Restriction During Lactation

Abstract: Neonatal protein restriction causes lower body weight and hormonal dysfunctions in 6 months-old rats. In this model, we studied the body composition, glycogen content, serum lipid, serum protein, and hormones related to glucose homeostasis in the offspring during development. At birth, lactating rats were divided into: control dams - fed a normal diet (23% protein) and protein restricted dams - fed a diet with 8% protein. After weaning, pups received normal diet. Offspring were killed at 21, 90, and 180 days-o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
35
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(42 citation statements)
references
References 25 publications
(38 reference statements)
6
35
0
Order By: Relevance
“…In accordance with our previous report (Fagundes et al 2009), LPHC animals had lower glycemia and insulinemia in 180-day-old rats. These findings, together with lower I/G ratio, HOMA-IR, and HOMA-b, indicate that these animals had higher insulin sensitivity.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In accordance with our previous report (Fagundes et al 2009), LPHC animals had lower glycemia and insulinemia in 180-day-old rats. These findings, together with lower I/G ratio, HOMA-IR, and HOMA-b, indicate that these animals had higher insulin sensitivity.…”
Section: Discussionsupporting
confidence: 93%
“…In recent years, it has been shown that long-term ER decreases the levels of oxidative damage to cellular macromolecules mainly by reducing the rate of mitochondrial reactive oxygen species (ROS) generation in rodents (Gredilla & Barja 2005). In contrast to chronic ER, studies in rats showed that maternal ER, during lactation only, programs the adult offspring to a higher body length and weight , while maternal protein restriction seems to protect against obesity and insulin resistance (Fagundes et al 2007(Fagundes et al , 2009.…”
Section: Introductionmentioning
confidence: 99%
“…This agrees with several studies showing that early malnutrition programmes lead to the development of a thrifty phenotype (Petry et al 2000, Ozanne & Hales 2002, Plagemann 2006. Interestingly, PR mice had higher total body fat, as previously detected in PR rats of the same programming model (Fagundes et al 2007(Fagundes et al , 2009). Thus, it is possible that the lower body mass of this group is due to a loss of muscle mass.…”
Section: Discussionsupporting
confidence: 92%
“…Table I shows the composition of the diets (Reeves et al 1993). The PR diet was produced in our laboratory, using the standard commercial diet for rodents (NuvilabNuvital Nutrientes SA, PR, Brazil) by replacing parts of the protein with cornstarch (Lisboa et al 2003, de Moura et al 2007, Fagundes et al 2009). The amount of cornstarch that was added compensated for the decrease in energy content due to protein reduction.…”
Section: Methodsmentioning
confidence: 99%
“…The insulin resistance index (IRI) was calculated by the product of fasting insulin (µIU/mL) × fasting glucose (mmol/L) (Fagundes et al 2009, Lima Nda et al 2011, Li et al 2012.…”
Section: Plasmatic Parametersmentioning
confidence: 99%